Stoicism among the Victorians? The Legacy of Old Norse Sagas in William Morris's Utopian Views of Humanity - SPINOZZI, Paola (University of Iceland Press, 2006)
Victorian intellectuals such as George Webbe Dasent, Thomas Carlyle, Matthew Arnold and William Morris studied Old Norse literature in order to retrace the origins of North Europe and to present the heroic code of behaviour as an ideal ethical model for the Victorians. Not unlike other intellectuals of his time, Morris thought of human beings that should rise to the stature and reflect the virtues of the saga heroes. However, his contribution to Victorian idealisations of a humankind shaped on Old Norse anthropological and sociological models involves enquiries which must be related to his utopian frame of mind. His reception of the sagas, re-examined from the vantage point of his attitude towards ethics and customs, reveals not only how the Old Norse code of behaviour affected his response to moral issues which vexed his own life, but also how it engendered a deeper philosophical and anthropological interrogation. A comparative reading of Morris’s The Story of Kormak, the Son of Ogmund (1870-1871, unpublished), and of The Lovers of Gudrun, a version of the Icelandic Laxdaela saga included in The Earthly Paradise (Part III, 1870), aims at clarifying how human strife in Icelandic settings stimulates his enquiry into the nature of man and woman. As Morris argues in his preface to the Saga Library, in his creative writings and also, with biographical overtones, in his letters, stoicism, which encompasses self-restraint, self-control, endurance, patience, magnanimity, and resignation, enables human beings to counteract fate, the shortness of life, the bitterness of love, sorrow and rage. Whether the acquisition of the Old Norse ethics of endurance can improve humankind is a crucial issue Morris never stops pondering about; how to channel the outburst of passions, how to master human drives and prevent them from constantly undermining social order and cohesion can well be regarded as a highly problematic issue he goes on exploring in News from Nowhere (1890) as well as in his late romances. Thus, if Morris’s ...